Work Environment, Supervision and Job Satisfaction on Employees Productivity of Manufacturing Firms in Oluyole Local Government Area, Oyo State, Nigeria. - Ajamobe, John Oluwaseun; Adeniyi, Samuel Oluwamuyiwa; Adeniyi, Oluwafisayo Grace (Sekolah Tinggi Manajemen IPMI, 2022)
The life wire of every organization is the quality of its workforce. Thus, employee’s productivity is an important consideration for the success of any business as it provides the needed competitive comparative advantage over rivalry firms in the market. In fact, understanding the peculiarity of every employee within an organization in term of work psychology geared towards bring the best out of each employee is as important as the organization itself. In the light of this basic truth, it is highly imperative that attempts be made at examining work environment, supervision and job satisfaction on employees’ productivity of manufacturing firms in Oyo State, Nigeria. The study aimed at examining the impact of work environment, supervision and job satisfaction on employees’ productivity in Nigeria. Three research hypotheses were formulated and tested at 0.05 significant levels to guide the study. Consequently, adopting the causal-comparative research design which is ex post facto in nature using purposive sampling technique, 466 manufacturing firms was the total population for the study in which 50% was sampled comprising 235 participants. However, only 202 participants returned their questionnaire given 86% which is high enough for analysis. The research instrument titled “Work Environment, Supervision and Job Satisfaction on Employees Productivity Questionnaire” (WESJSEPQ) was validated to gather data in the study at .85 reliability value. The data collected was analyzed using descriptive statistics such as frequency coefficient, percentage, mean and standard deviation while Pearson Product Moment Correlation was used to test the three hypotheses. Findings of the study showed that work environment (r= -.92; df= 193; P <.05), supervision (r= .791; df= 193; P <.05) and job satisfaction (r= .679; df = 193; P < .05) were significantly correlated with employees’ productivity. The study recommends that workers welfare and supervision should be of paramount importance to the management of manufacturing firms which will translate to increased productivity.